Implementation of the Deep Learning Approach in Developing Students' Critical Thinking Abilities in Economics Learning in Grade X of SMAS PGRI 2 Sampit - Dhea Fatmala; Apuannor Apuannor; Sudarmono Sudarmono (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aims to analyze the effect of the Deep Learning approach on students’ critical thinking skills in Economics subjects for Grade X students at SMAS PGRI 2 Sampit. Critical thinking is one of the essential 21st-century competencies that needs to be developed to enable students to face various complex problems. In practice, economics learning is still often teacher-centered, causing students to memorize concepts without fully understanding their meaning. The Deep Learning approach serves as an alternative learning strategy that emphasizes meaningful, reflective, contextual, and student-centered learning. This study employed a qualitative descriptive method with data collection techniques including observation and interviews. The findings revealed that the implementation of the Deep Learning approach was able to improve students’ understanding of economic concepts, increase their active participation in learning activities, enhance their ability to analyze economic problems, develop their ability to express opinions logically, and strengthen their self-confidence. These findings indicate that Deep Learning can be an effective learning strategy for improving students’ critical thinking skills in Economics subjects.